The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1152/ajpregu.00183.2010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pulmonary system limitations on locomotor muscle fatigue in patients with COPD

Abstract: We examined the effects of respiratory muscle work [inspiratory (W r-insp); expiratory (W r-exp)] and arterial oxygenation (SpO 2 ) on exerciseinduced locomotor muscle fatigue in patients with chronic obstructive pulmonary disease (COPD). Eight patients (FEV, 48 Ϯ 4%) performed constant-load cycling to exhaustion (Ctrl; 9.8 Ϯ 1.2 min). In subsequent trials, the identical exercise was repeated with 1) proportional assist ventilation ϩ heliox (PAV); 2) heliox (He:21% O 2); 3) 60% O 2 inspirate (hyperoxia); or 4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
145
2
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(166 citation statements)
references
References 69 publications
(80 reference statements)
8
145
2
11
Order By: Relevance
“…This seems to be in line with previous findings of Amann et al 39 , who reported that the high susceptibility to lower-limb muscle fatigue in patients with COPD is in part attributable to insufficient oxygen transport as a consequence of exaggerated arterial hypoxemia and/or excessive respiratory muscle work. Moreover, quadriceps muscle strength was positively related to D L CO in patients with COPD 18 .…”
Section: Discussionsupporting
confidence: 93%
“…This seems to be in line with previous findings of Amann et al 39 , who reported that the high susceptibility to lower-limb muscle fatigue in patients with COPD is in part attributable to insufficient oxygen transport as a consequence of exaggerated arterial hypoxemia and/or excessive respiratory muscle work. Moreover, quadriceps muscle strength was positively related to D L CO in patients with COPD 18 .…”
Section: Discussionsupporting
confidence: 93%
“…The perception of fatigue has to be differentiated with objective measurements of fatigue. Most of the studies examining muscle fatigue after exercise in COPD have used a nonvolitional technique: twitch measurement after magnetic stimulation (240,250,(264)(265)(266)(267)(268). Additionally, the EMG median frequency represents a valuable indirect marker to predict contractile fatigue (269).…”
Section: Limb Muscle Function In Copdmentioning
confidence: 99%
“…During strenuous exercise, peripheral vasoconstriction associated with the high demand for respiratory muscle blood flow appears to compromise limb muscle perfusion (261,425,426) and consequently enhance muscle fatigue (427). A blood redistribution phenomenon in favor of the respiratory muscles may also occur in COPD (428), and it has been hypothesized that strategies that reduce respiratory muscle work may alleviate limb muscle fatigue by restoring blood flow to the limb muscles (267,429). This hypothesis was supported by a study from Amann and coworkers, who gave a range of interventions designed to improve oxygenation (by supplemental oxygen) and/or reduce work of breathing (proportional-assist ventilation or helium or both) (267).…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…Clinically, respiratory muscle fatigue could play an important role in limiting oxygen delivery in patients with obstructive sleep apnea (OSA) (1,24), chronic heart failure (18), and chronic obstructive pulmonary disease (COPD) (2). It is still unclear whether diaphragm fatigue, thereby metaboreflex, leads to alternations in sympathetic nerve activity and cardiovascular variables during dynamic leg exercise at submaximal intensity.…”
mentioning
confidence: 99%